PERANCANGAN DAN PEMBUATAN JIG PADA PROSES DRILLING KONEKTOR RANGKA KURSI DI PT. ANEMATO GUNA SADAYA SUMEDANG - Agung Budiman (PROCEEDING STIMA)
A jig is a special tool that serves to hold, hold, placed on the workpiece to keep the workpiece positioning the workpiece so that the manufacturing process of a product can be more efficient. Therefore, the author tries to make the position of the hole into the center of the seat chassis connectors, designing and making Jig Drill chair connector construction and selecting the Jig Drill material.After Jig created the author got some conclusions that are making the location of the hole into the center of the chair frame connector, that is by using the tools or Jig production process, the design of the chair frame connector by doing, observation of the dimensions of the seat chassis connectors, determine the surface parts to be clamped, and do the design with Software Solid Works, and the selection of Jig Drill material is by comparison, the material of Jig Drill must be stronger than the workpiece that is Brinell hardness for aluminum is 70HB and Tensile Strength value for aluminum is 345Mpa, while SCM440 Brinell hardlines is 217HB and Tensile Strength for SCM440 steel is 980Mpa, so the jig drill strength is harder than the workpiece. The result of Jig made is Jig able to grip the workpiece well, drill hole results by using jig into a center and shorten the drilling process time on the seat frame connector and consistent results. Jig is a special tool that serves to hold, hold, placed on the workpiece to keep the workpiece positioning the workpiece so that the manufacturing process of a product can be more efficient. Therefore, the author tries to make the position of the hole into the center of the seat chassis connectors, designing and making Jig Drill chair chair connector construction and selecting the Jig Drill material.After Jig created the author got some conclusions that is making the location of the hole into the center of the chair frame conenktor, that is by using the tools or Jig production process, the design of the chair frame connector by doing, observation of the dimensions of the seat chassis connectors, determine the surface parts to be clamped, and do the design with Software Sholid Works, and the selection of Jig Drill material is by comparison, the material of Jig Drill must be stronger than the workpiece that is brinell hardnes for aluminum is 70HB and Tensile Strength value for aluminum is 345Mpa, while SCM440 brinell hardnes is 217HB and Tensile Strength for SCM440 steel is 980Mpa, so the jig drill strength is harder than the workpiece. The result of Jig made is Jig able to grip the workpiece well, drill hole results by using jig into center and shorten the drilling process time on the seat frame connector and consistent results.